Implementasi Rally Coach Untuk Mengembangkan Keterampilan Berpikir Kritis Pada Pelajaran Matematika - Joko Krismanto Harianja (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Critical thinking skills need to be developed in learning activities because these skills are needed by students especially in solving problems both in everyday life and for the future. Based on research that has been done, students' critical thinking skills can be developed by implementing the rally coach learning model in mathematics learning activities. Rally coach is a cooperative learning model. From the research results obtained using descriptive research methods with a qualitative approach, students' critical thinking skills have increased significantly which indicates that the implementation of the rally coach learning model was declared successful. This study has been done using CAR (Class Action Research) method with 4 cycles. As part of the research, to find out an increase in accordance with expected, researchers designed a test instrument that has been tested for validity and reliability using the content validity ratio (CVR) method and the Cronbach Alpha formula. The results that have been obtained show in detail that the rally coach learning model provides an excellent contribution to improving students' critical thinking skills.